Early Warning Alarm System for Detecting Forest Fire Using NODE MCU with IoT (International Journal of Innovative Research in Computer Science & Technology, 2022)
Wildfire causes a severe impact on the  ecosystem may. It has occurred naturally or manmade.  Nowadays, the construction of buildings takes place  everywhere, even in the forest surrounding region also. So  the surrounding people have to face a lot of troubles through these forest fires. Sometimes it leads to serious  health issues as a natural wildfire cannot be avoided but  can be timely detected and dealt with by effectively using  the available technologies. The Internet of things comes to  mind as a first choice due to its special features. Our project  sensor is used to detect the fire by Node MCU information  is updated continuously through a cloud, and that  information can be checked remotely by an android  application. Also, we are using Buzzer so that nearby  people can be alerted. Thereby we can take timely action  so that many natural resources and human beings will be  saved from this threat.
Keywords: Ecosystem; Technologies; Node MCU; Natural Resources; Internet of Things